2022
DOI: 10.31635/ccschem.021.202100802
|View full text |Cite
|
Sign up to set email alerts
|

Radical Mechanism of Ir III /Ni II -Metallaphotoredox-Catalyzed C(sp 3 )–H Functionalization Triggered by Proton-Coupled Electron Transfer: Theoretical Insight

Abstract: Photoredox catalysis can be induced to activate organic substrates or to modulate the oxidation state of transition-metal catalysts via unique single-electron transfer processes, so as to achieve challenging C(sp 3 )−H functionalization under mild conditions. However, the specific reaction mechanism and relevant electron transfer process still need to be clarified. Here, a highly regioselective Ir III /Ni II -metallaphotoredox catalyzed hydroalkylation of unsymmetrical internal alkyne with ether α-hetero C(sp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In recent years, the reaction mechanism of photo-redox catalysis has been systematically studied through experimental and theoretical methods. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nonetheless, two important issues involved in the reaction remain obscure: (i) Is the C(sp 3 )-H activation of 1 by excited decatungstate realized by a general stepwise PCET or direct HAT process? (ii) What is the origin of regioselectivity of radical addition?…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the reaction mechanism of photo-redox catalysis has been systematically studied through experimental and theoretical methods. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nonetheless, two important issues involved in the reaction remain obscure: (i) Is the C(sp 3 )-H activation of 1 by excited decatungstate realized by a general stepwise PCET or direct HAT process? (ii) What is the origin of regioselectivity of radical addition?…”
Section: Introductionmentioning
confidence: 99%
“…The Stuttgart–Dresden–Bonn basis sets were employed for valence electrons of Pd atoms with corresponding effective core potentials representing their core electrons, and 6-31G­(d) basis sets were employed for other atoms. The solvation effect (toluene) was evaluated with the polarizable continuum model (PCM). We also compared the PCM model with the solvation model based on density (SMD), as described in page S6 and Table S6 of the SI and found that the barrier of Ph–F bond activation in the SMD model differs little with that in the PCM model. We also made benchmark calculations on basis set as shown in SI.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, while oxidative quenching cycles (Fig. 1D) have been proposed in the literature occasionally with regards to Ni/PC dual catalytic C─C, C─O, C─N, or C─S bond forming systems, sometimes with computational support, [17][18][19][20][21] experiments capable of distinguishing between oxidative quenching, reductive quenching, and energy transfer (see reviews for relevant spectroscopic and electrochemical methods) [22][23][24] have not been performed in the study of these systems.…”
Section: Introductionmentioning
confidence: 99%